Scientific Word v2.0 and Scientific WorkPlace v2.0. - Shone, Ronald (Economic Journal, 1995)
A review of Scientific WorkPlace (SWP), a software program that allows text and mathematical manipulation. The range and facilities of SWP, its printing and styles, its hardware and software requirements, and a number of criticisms of the program are outlined.